(untitled) (Świat Idei i Polityki, 2013)
The international documents, especially Lisbon Strategy and Europe 2020 strategy, oblige Polish government to the implementation of the principles of the sustainable development in the employment policy. Analysis of Polish and European employment strategies are pointing that priority like: just, free from poverty, equal opportunities for women, men and young people on the labour market, economic activity of older people, protection of the environment or harmfulness of the work to the environment, proving that they are not effectively carried out in Poland. Employment policy is also ineffective, because the main strategies are not taking into account attitudes of Poles to the work, and values which are shaping this attitude. Return to values is extremely important for the implementation of sustainable development, because for this idea, values shape human and social reality, thus work reality.